Keratinocytes contribute to the recruitment and M1 polarisation of macrophages during C. albicans colonisation - Guan, Xiu-Hao; Hong, Yu-Xiao; Qi, Rui-Qun; Gao, Xing-Hua (Cellular and Molecular Biology, 2018)
Candida albicans (C. albicans) is an opportunistic human fungal pathogen that colonises the skin. Both keratinocytes and macrophages play crucial roles in host defence against C. albicans. However, the interaction of keratinocytes with macrophages during C. albicans colonisation has not been well studied. In this study, macrophages were cultured in conditioned medium from keratinocytes treated with heat-inactivated C. albicans (CM-C. albicans), macrophage migration and polarised activation and were then assessed by a Transwell assay, flow cytometry, quantitative real-time PCR (qPCR), Western blot and an enzyme-linked immunosorbent assay (ELISA). The results showed that CM-C. albicans-stimulated macrophages display significantly increased migration and phagocytosis, and they display an upregulation of proinflammatory cytokines (tumour necrosis factor alpha (TNF-a), interleukin (IL)-12 and nitric oxide (NO)). Markers characteristic of M1 macrophages, such as human leukocyte antigen (HLA)-DR, CD86 and inducible nitric oxide synthase (iNOS), are upregulated, whereas markers of M2 macrophages, such as mannose receptor (MR) and Arginase 1 (Arg1), are not affected. Additionally, the levels of TNF-a, IL-12 and monocyte chemotactic protein 1 (MCP-1) in CM-C. albicans are markedly upregulated, whereas the levels of IL-4 and IL-10 are not affected. And the CM-C. albicans-induced M1 macrophage polarisation, proinflammatory cytokine production and phagocytosis could be blocked by an anti-TNF-a neutralising antibody. This study showed that keratinocytes may promote macrophage recruitment and M1 polarisation during C. albicans colonisation at least in part by secreting TNF-a.